2022
DOI: 10.1103/physreve.105.064802
|View full text |Cite
|
Sign up to set email alerts
|

Effects of orientational order on modulated cylindrical interfaces

Abstract: Cylindrical interfaces occur in sheared or deformed emulsions and as biological or technological lipid monolayer or bilayer tubules. Like the corresponding spherical droplets and vesicles, these cylinder-like surfaces may host orientaional order with n-fold rotational symmetry, for example in the positions of lipid molecules or of spherical nanoparticles. We examine how that order interacts with and induces shape modulations of cylindrical interfaces. While on spherical droplets 2n topological defects necessar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…First, the small-r cylindrical shapes have a lower surface area. Thus, the number of structural defects (coupled to possible fluctuations of Gaussian curvature 41 ) and surfaceadsorbed impurities is smaller, so that the structure of the interfacial crystal is closer to being perfect and its Y 2D is higher. Another possibility is that the unscreened electrostatic fields due to the charged head groups of the interfacial surfactants penetrate through the bulk oil of the small-r droplets, 42 so that the ensuing electrostatic contribution modifies the elastic moduli.…”
Section: T H Imentioning
confidence: 99%
“…First, the small-r cylindrical shapes have a lower surface area. Thus, the number of structural defects (coupled to possible fluctuations of Gaussian curvature 41 ) and surfaceadsorbed impurities is smaller, so that the structure of the interfacial crystal is closer to being perfect and its Y 2D is higher. Another possibility is that the unscreened electrostatic fields due to the charged head groups of the interfacial surfactants penetrate through the bulk oil of the small-r droplets, 42 so that the ensuing electrostatic contribution modifies the elastic moduli.…”
Section: T H Imentioning
confidence: 99%
“…Examples include the effects of different types of lipids [2130] polymers [3135] nanoparticles [3640] phospholipid-surfactant mixtures [41], protein pumps [20, 42], adsorbed BAR proteins [4348] inter-calated curvature-inducing proteins [4951] and crowds of sterically-repelling proteins [5256] (see also reviews in [5759] Generally speaking, the total free energy of such systems contains, besides the Helfrich free energy, the free energy of the particles and a term accounting for the interaction of the membrane with the particles. Expressions for the free energy of the particles often contain terms penalising phase boundaries [22, 41, 43, 49, 60] and terms accounting for interactions between the particles and for entropy, either through a Flory-Huggins theory for a mixture of occupied and unoccupied sites [21, 27, 33, 41, 43], or a Ginzburg-Landau expansion thereof [22, 49, 61]. To describe the interaction of particles with a vesicle, most authors [21, 22, 33, 35, 41, 43, 46, 4951, 60, 62, 63] considered a linear coupling ∝ Λ Hϕ of the mean curvature H to the areal particle density ϕ with a coupling parameter Λ. Leibler showed that such interaction between proteins and a flat membrane sheet changes its effective bending rigidity to κ− Λ 2 /a , with a setting the strength of mutual protein interactions [49].…”
Section: Introductionmentioning
confidence: 99%